Defining the Phases of Boxing Punches: A Mixed-Method Approach. Issue 4 (April 2020) - Lenetsky, Seth; Brughelli, Matt; Nates, Roy J.; Neville, J.G.; Cross, Matt R.; Lormier, Anna V.
Abstract : Abstract: Lenetsky, S, Brughelli, M, Nates, RJ, Neville, JG, Cross, MR, and Lormier, AV. Defining the phases of boxing punches: A mixed-method approach. J Strength Cond Res 34(4): 1040–1051, 2020—Current research on punching in boxing has explored both kinematic and kinetic variables; however, there is no shared structure in the literature to describe these findings. A common method used to provide a shared structure in other sporting tasks is the definition of movement phases. To define the phases of 4 punches used in boxing (lead punches and rear straight and hook punches), 10 experienced and competitive boxers (age = 25.6 ± 5.97 years, height = 179.5 ± 7.72 cm, body mass = 95.66 ± 21.82 kg, and years training = 10.3 ± 5.97 years) were tested while performing maximal-effort punches. Ground reaction forces (GRFs), electromyographic, high-speed video (HSV), and striking dynamometry data were collected during all punches. A mixed-method approach was used to define the phases for each punch type based on the GRF measurements and impact timing from the striking dynamometer. Electromyographic and HSV data were then used to develop a more holistic understanding of punching actions by elaborating on the description of each phase. The final outcome of this approach has produced definitions for the phases of straight and hook punches, a greater qualitative understanding of said punches, and most importantly, a structure for current and future punching-related research, and a context to improve coach/sport scientist communication.